PENERAPAN PERYATAAN STANDAR AKUNTANSI KEUANGAN NOMOR 46 TENTANG AKUNTANSI PAJAK PENGHASILAN DAN UNDANG-UNDANG NOMOR 36 TAHUN 2008 TENTANG PAJAK PENGHASILAN ATAS PAJAK PENGHASILAN BADAN PADA PT.MEGA JASAKELOLA - Letlora, Ray Marcel; Tinangon, Jantje J.; Kalangi, Lintje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
The application of PSAK No. 46, Accounting for Income Taxes expected to bridge between accounting and tax laws with provisions. The purpose of this study is to investigate the application of PSAK No. 46 and Act No. 36 of 2008 on corporate income tax on PT.mega Jasakelola. The analytical method used is descriptive analysis. The application of PSAK No.46 of research results 46 top corporate income tax has been applied on PT.Mega Jasakelola especially regarding deferred tax, taxable income and tax payable now. Implementation of Act No. 36 of 2008 on income tax on business services is appropriate PT Mega Jasakelola Taxation existing regulations. PT.Mega Jasakelola has implemented reporting income tax on their annual tax return, in accordance with the provisions of this is evidenced by the positive correction done at the expense of the non- taxable.